A STUDY TO EVALUATE THE EFFECTIVENESS OF INFORMATION, EDUCATION, AND COMMUNICATION ON MALARIA AND ITS PREVENTION AMONG PEOPLE RESIDING AT UDALPUR VILLAGE, MEHSANA - K Muniamma Devi, Dr N.Siva Subramanian , Manknojiya Danis , Mevada Reena , Desai Nikita, Gandhi Muskan, Mansuri Alshifa, Mansuri Sayma, Makvana Dipika (South Eastern European Journal of Public Health, 2025)
Background: Malaria is a major public health problem, especially in rural settings with poor access to health information. Information, Education, and Communication (IEC) activities are important in enhancing knowledge and awareness of malaria prevention and control. The current study sought to evaluate the effectiveness of IEC in increasing malaria awareness among people living in Udalpur village. Methods: A one-group pretest-posttest pre-experimental research design was utilized, wherein a sample size of 30 participants was identified using a non-probability convenient sampling approach. A standard self-administered questionnaire assessed the level of knowledge among the participants prior and subsequent to IEC intervention. Descriptive as well as inferential statistics viz. mean, standard deviation, and paired t-test were employed to analyze data in order to determine the outcome of the intervention. Results: Pretest results showed that 50% of the respondents had poor knowledge, 26.66% had moderate knowledge, 16.66% had average knowledge, and a mere 6.66% had good knowledge about malaria and its prevention. After the intervention, a tremendous improvement was noted with 40% of the respondents showing good knowledge and the poor knowledge reducing to 10%. The average knowledge score went up from 4.3 (SD = 2.9) during the pretest to 20.56 (SD = 3.33) during the posttest with a statistically reliable t-value of 21.6165 (p < 0.05). Conclusion: The results reaffirm that IEC interventions greatly improve malaria prevention knowledge. The inclusion of such educational measures in community health programs can successfully curb malaria and enhance health practices.